DAMPAK RELAKSASI PROGRESIF PADA KLIEN YANG MENGALAMI KECEMASAN DAN MASALAH TIDUR SEBELUM PELAKSANAAN OPERASI KOLOSTOMI DI RUANG 19 DAN 17 RSU Dr. SAIFUL ANWAR MALANG - Andi Eka pranata (LPPM Universitas dr. Soebandi, 2013)
Anxiety is a bad condition or situation if looked of phsycological human. Every human always life by anxiety, although the good life. By anxiety, we will be strong human and will life is better than before. Pre operation condition make somebody are anxiety and have any problem to healths. Pshycological factor influence preparedness of operation patient. This condition will be make it condition as well as health. The blood pressure will be higher than normal condition, heart rate is tachicardia, peristaltic movement will be faster than before, and any abnormality vital sign exercise. Not only that, sleeping cycle patients are disturb. So, nursing must be thinking for problem solving this condition to perfect this wellness. Progressive relaxation is a method to make our body are relax. This methods have step by step to do it. This methods are combine between respiratory system and motor system. This research using case study system, so only looking for and using methods descriptive every moment and condition of patient. Case study not require analize, but looking for relevance beteween scientific and practice knowledge. So, this product of research will be technique to reduce anxiety effect. This research using colostomy pre operative patient and have anxiety and sleep cycle problem. For this research was know about anxiety and sleep of pre operative colostomy patient are anxiety and can’t sleep by good. This patient are 2 person and of twice patient is same conditions. After that, author doing progressive realxation and as long time do exercise about anxiety and sleep cycle. Is good product, anxiety and sleep cycle back to normal. Progressive relaxation will make fresh body, blood circulation by good and couple nervus is good. If oxygenation in the circulation nothing obstruction (oclusion, spasme, trombosis), so oxygen will normal transfer of tissue. The brain be fresh by good circulation and endorphin will not at circulation. If this condition really at patient, so pre operative conditions never by anxiety and sleep cycle will be normally.